PENGEMBANGAN E-MODUL MATEMATIKA BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA KELAS VIII SMP NEGERI 1 PADANG BOLAK - Simamora, Josua; Harahap, Muhammad Syahril; Siregar, Eva Yanti (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to create and test the quality of a math e-module that incorporates ethnomathematics to improve students' mathematical literacy. This is a development study that follows the ADDIE development model, which includes five stages: analyze, design, development, implementation, and evaluation. The research involved 25 students. The findings showed that the experts rated the e-module at an average score of 80.2%, which is considered valid. The e-module was also found to be very practical based on the student questionnaire score of 89.72%. Its effectiveness was proven with 100% of students achieving over 85% in the mathematical literacy test. Based on these results, it can be concluded that the developed ethnomathematics-based math e-module for the topic of systems of linear equations in two variables is suitable to be used as a learning material.